Left ventricular remodelling and diastolic dysfunction in mitral valve prolapse - E. G. Malev; A. P. Pshepyi; L. V. Vasina; S. V. Reeva; E. V. Timofeev; A. L. Korshunova; E. V. Zemtsovskyi (Российский кардиологический журнал, 2013)
Aim. To assess the severity and potential mechanisms of left ventricular (LV) myocardial remodelling and diastolic dysfunction in symptom-free young patients with mitral valve prolapse (MVP), but no arterial hypertension or significant mitral regurgitation. Material and methods. The study included 78 patients with MVP (mean age 19,7±1,6 years; 72% males). The control group, comparable by age and sex distribution, included 80 healthy people. Longitudinal diastolic strain rate (SRe) was assessed using the speckle tracking method (Vivid 7 Dim, EchoPAC’06, GE). Serum levels of transforming growth factors (TGF)